Синтаксическая модель NVN2 prep. N3 как средство выражения посессивнocти - Григалюнене, Йоне (Kalbotyra, 1987)
The purpose of this paper is to propose an analysis for the construction NVN2 prep. N3 which may be called possessive because a part-whole relation is necessarily implied between N2 and N3. An attempt is made to specify the circumstances under which the subject of the action (expressed by the of touching) coming into contact with a part of an object may be said to be contacting with the whole of it. The present paper also touches upon the problem of the notion of object. At present there is no adequate linguistic theory of object. We propose an interpretation according to which the grammatical object in the construction discussed is regarded as the true object of the action and therefore it cannot be considered irrelevant to “deep syntax”. An attempt has been made here to revise and enlarge the list of verbs used in the said construction.